WOMEN AND DERADICALISM: UNDERSTANDING THE WOMEN’S ROLE IN DEVELOPING PEACEFUL CULTURE - Wanda Fitri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
The development of scholars, sects in Islam thought is being proof of the development of Muslims as demanded to be respectful of the differences from the beginning. In Indonesia, since the formation of the NKRI, the most important sacrifice made by the founders (Muslims) is concerned with unity. The unity in togetherness, kinship, and respect for diversity, not group individualism, intellectualism, materialism makes Islam as the state ideology even though most of the people are Muslims. As the largest Muslim majority in the world, Indonesia is inseparable from the threat of radicalism and terrorism. The multiethnic and religious social life of Indonesia are being triggers prejudice among the religious groups. Intolerant attitude in responding to the differences is often shown by different groups which tends to trigger radicalism that leads to violence in the form of acts of terror in the name of religion (Islam). Unfortunately, in various acts of radicalism, women are the victims. The problem is whether womenonly become passive victims, even though women have strategic roles in eroding and suppressing radicalism. Various studies have proven how women play a large role in the process of building diversity and a culture of peace. This paper expected to see women as survivors, peace activists / activists, and peace agents whose actions cannot be ignored both psychologically and socially.